Effectiveness of the Online Storytelling Program from Home at the Makassar City Library Service - Iffa Alfiyyah Septianty; Herlina Sakawati; Sulmiah; Anisa Fitri (Perkembangan Kajian Sosial, 2025)
Digital libraries play a very important role in facilitating access to information in the digital era, but libraries, especially in public services, still face various major challenges, especially in developing countries such as Indonesia. This study aims to analyze the effectiveness of the Online Mobile Fairy Tale Program from Home (DONGKELOR), which was launched by the Makassar City Library Office in 2020, in improving children's literacy through online fairy tales during the Covid-19 pandemic. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The effectiveness of this program is evaluated based on three indicators put forward by Duncan, namely goal achievement, integration, and adaptation. The results of the study show that despite facing operational constraints such as budget and facility limitations, DONGKELOR managed to achieve the main goal of increasing children's interest in reading and introducing digital libraries. This program has also proven to be successful in integrating various parties and social media platforms to expand the reach of the audience, as well as being able to adapt quickly to changes and limitations that arise during the pandemic. However, the year-on-year decline in viewership shows the need for further evaluation and improvement. Therefore, it is recommended that the Makassar City Library Office conduct periodic evaluations, strengthen cooperation with various parties, and develop interactive features to attract more participation from the audience. This research is expected to contribute to the development of more effective digital library services in the future.